The Influence Of Job Training, Work Experience, And Competency On The Performance Of Italian Restaurant Kitchen Employees In South Jakarta - Goeltom, Vasco Adato H.; Juliana, Juliana; Kristabella, Cheryl; Florency, Gaby (SEAN Institute, 2024)
The main objective of this study is to examine and assess how job training, work experience, and knowledge competency impact the performance of kitchen staff working at Italian Restaurants in South Jakarta. Therefore, the researchers aims to identify various factors that can influence the performance of kitchen employees at the Italian Restaurants in Sount Jakarta. non- probability sampling, which focuses on the targeted Italian Restaurant kitchen staff in South Jakarta, is utilized for data collection where sampling is not random and is aimed specifically at the population. This sampling technique is done freely according to the wishes of the researcher. A total of 150 respondents were included in this study, and questionnaires were distributed to gather primary data. Secondary data from articles, journals, and books were also used. The data analysis employed in this research is multivariate analysis, while the research hypothesis was tested by applying the Structural Equation Model (SEM) approach, using Partial Least Squares (PLS). The findings demonstrate that job training, work experience, and knowledge competency all have a positive impact on employee performance